2020
DOI: 10.3390/ma13143055
|View full text |Cite
|
Sign up to set email alerts
|

Floating Ni Capping for High-Mobility p-Channel SnO Thin-Film Transistors

Abstract: We utilized Ni as a floating capping layer in p-channel SnO thin-film transistors (TFTs) to improve their electrical performances. By utilizing the Ni as a floating capping layer, the p-channel SnO TFT showed enhanced mobility as high as 10.5 cm2·V−1·s−1. The increase in mobility was more significant as the length of Ni capping layer increased and the thickness of SnO active layer decreased. The observed phenomenon was possibly attributed to the changed vertical electric field distribution and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In this case, I ph is suppressed because the space available for carrier generation is limited and the channel resistance is high. [19][20][21] Reducing the carrier concentration (n) in the channel layer of TFT based UVPDs, or using a Schottky metals (e.g., Pt, 22,23) Au, 24) and Ni 25) ), or p-type MOSs (e.g., NiO, [26][27][28] MgO, 29) and Cr 2 O 3 30) ) as a capping layer (CL) on the channel surface (i.e. the back channel) have been demonstrated to mitigate the trade-off between I dark and I ph .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, I ph is suppressed because the space available for carrier generation is limited and the channel resistance is high. [19][20][21] Reducing the carrier concentration (n) in the channel layer of TFT based UVPDs, or using a Schottky metals (e.g., Pt, 22,23) Au, 24) and Ni 25) ), or p-type MOSs (e.g., NiO, [26][27][28] MgO, 29) and Cr 2 O 3 30) ) as a capping layer (CL) on the channel surface (i.e. the back channel) have been demonstrated to mitigate the trade-off between I dark and I ph .…”
Section: Introductionmentioning
confidence: 99%
“…Tin monoxide (SnO) is considered one of the most promising p-type oxide semiconductors, because of its spherical Sn 5s orbitals which are comparable with the energy levels of O 2p orbitals. They can form the pseudo-closed ns 2 orbitals in SnO through the hybridization and delocalization to provide an effective path for hole conduction, giving it a small m h * [4,5]. Furthermore, SnO with a large direct optical bandgap (2.5-3.4 eV) makes it an excellent hole conduction candidate for transparent electronics [6].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous report, we demonstrated that the formation of a Ni capping layer can increase the field-effect mobility ( μ FE ) of p-channel SnO TFTs. This was attributed to the changed vertical electric field distribution and increase in the hole concentration inside SnO [ 34 ]. In this study, we compared the electrical performance and stability of p-channel SnO TFTs consisting of capping layers with different metals (Al, Ni, Pt, and Cr) to thoroughly understand the effects of a metal capping layer on p-channel SnO TFTs.…”
Section: Introductionmentioning
confidence: 99%